2012
DOI: 10.7314/apjcp.2012.13.11.5875
|View full text |Cite
|
Sign up to set email alerts
|

PPAR-Gamma Pro12Ala Polymorphism and Gastric Cancer Risk in a Turkish Population

Abstract: Background: Peroxisome proliferator-activated receptor gamma (PPARγ) is a ligand dependent transcription factor involved in various processes, including carcinogenesis. We aimed to investigate any possible association of the PPARγ Pro12Ala (rs1801282) polymorphism with risk of developing gastric cancer (GC). Patients and Methods: A hospital based case control study was designed covering 50 patients with GC and 120 healthy controls. The frequencies of PPARγ Pro12Ala (rs1801282) were determined using a polymeras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 12 publications
2
5
0
2
Order By: Relevance
“…As mentioned, PPARγ as a host gene plays important role in H. pylori-associated gastric carcinogenesis and (LIAO et al, 2006;Canbay et al, 2012). In our study, frequency of GG genotype and GC genotype were 33.7% and 40.8%, respectively.…”
Section: Discussionsupporting
confidence: 54%
“…As mentioned, PPARγ as a host gene plays important role in H. pylori-associated gastric carcinogenesis and (LIAO et al, 2006;Canbay et al, 2012). In our study, frequency of GG genotype and GC genotype were 33.7% and 40.8%, respectively.…”
Section: Discussionsupporting
confidence: 54%
“…One article was excluded for repeat studies based on the same population (Liao et al, 2007). Finally, a total of 5 case-control studies (Liao et al, 2006;Prasad et al, 2008;Tahara et al, 2008;Bazargani et al, 2010;Canbay et al, 2012) including 546 cases and 827 controls were identified for further analysis. There were 2 studies of Asians (Liao et al, 2006;Tahara et al, 2008), 3 of Caucasians (Prasad et al, 2008;Bazargani et al, 2010;Canbay et al, 2012).…”
Section: Study Characteristics and Meta-analysis Resultsmentioning
confidence: 99%
“…However, other similar observations could not draw such conclusion in prostate cancer (Paltoo et al, 2003;Zmuda et al, 2006), lung cancer (Campa et al, 2004), endometrial cancer (Paynter et al, 2004) and ovarian cancer (Pinheiro et al, 2010). On the contrary, recent studies found that Pro12Ala polymorphism increased the risk of gastric cancer (Canbay et al, 2012). Although there have been several studies investigating this Pro12Ala polymorphism with gastric cancer risk, due to the small sample size of the each study, it is not sufficient to form a reliable conclusion, so, we performed a meta-analysis to investigate these associations.…”
Section: Introductionmentioning
confidence: 90%
“…Deletion of KLF5 can result in a decrease in PI3K/AKT signaling and accumulate HIF1 α in prostate tumors to promote tumor angiogenesis [40]. Previous research has illustrated that the PPAR γ allele may be involved in the development, differentiation, and metastasis of gastric cancer in Turkey [43]. Sphk1 has been shown to be involved in the pathogenesis of human hepatocellular carcinoma (HCC), and DMS can inhibit the effects of Sphk1.…”
Section: Discussionmentioning
confidence: 99%